Design, development, and optimization of bio-mechatronic engineering products - Kumar, K. 1968-; Davim, J. Paulo (IGI Global, 2019)
"This book explores the design and development of bio-mechanical engineering products across the globe"-- Provided by publisher.
Keywords: Prosthesis -- Design and construction.; Orthopedic apparatus.; elektronické knihy; electronic books